Preferensi dan Kepuasan Petani Terhadap Penggunaan Benih Padi Unggul Jenis Ciherang di Desa Aras Kabu Kecamatan Beringin Kabupaten Deliserdang - Adriansyah, Adriansyah; Fuad, Fuad; Hakim, Mukti; Sulistia, Sulistia (UNIVERSITAS LABUHANBATU, 2023)
In Indonesia, rice is the main food crop besides corn, sago and tubers. The choice of rice as the main source of carbohydrates is because rice has superior plant characteristics when compared to other carbohydrate sources. In cultivating seed crops to be one of the main factors that determine success. Much of the increase in rice production has been supported by quality (certified) seed farmers. Rice production in North Sumatra in 2021 amounted to 2,126,765 tons of dry milled grain (GKG) experienced an increase in production of 330,665 tons compared to 2020, in 2004 rice production in North Sumatra only reached 1,796,100 tons. The increase in production was due to an increase in the harvested area of 424,650 hectares in 2021, when compared to the harvested area in 2020, namely the harvested area of only 366,590 hectares. think about the expected performance (results), if the performance is below expectations, the customer is not satisfied. If the performance meets expectations, the customer is satisfied. If the performance exceeds expectations, the customer is very satisfied or happy. This research was conducted in the village of Aras, District of Deli Serdang, using the non-probability sampling method. The results showed that farmers' preferences and satisfaction with the attributes of planting rice using Ciherang seeds were sufficient to satisfy farmers.Â Keywords: Rice, Chiherang, Satisfaction, farmers